Pembinaan Akhlak Bagi Remaja Dusun Teluk Melalui Kajian Taklimul Mutaallim - Sholihan (CV Putra Publisher, 2024)
Morals have a very important position, because morals are one of the pillars of religion. This can be seen from the source of morals, where the source of morals comes from revelation. Therefore, moral development at a young age is very important to ensure that they can develop into individuals who are ethical and have noble character. Therefore, a moral development program for teenagers through the study of Taklimul Mutaallim is really needed because the book Taklimul Mutaallim, a classic book in Islamic education, offers practical guidance on ethics and morals in the learning process. This book emphasizes the importance of sincere intentions, patience, perseverance, and respect for teachers and knowledge. These values ​​are very relevant in shaping the character of teenagers in the modern era who are often faced with various negative influences. The method used in this service is a service learning strategy. Service learning is a teaching and learning strategy that is carried out by integrating learning carried out in the classroom with community needs and problems. Meanwhile, the results of this service can have a positive impact not only on teenagers but also on society. The impact felt by the community after this activity is as follows: first, the return of the values ​​of honor and manners, second, increased involvement of teenagers in social activities, third, improved relations between generations